PENGARUH KEADILAN PERPAJAKAN, SISTEM PERPAJAKAN, DISKRIMINASI PERPAJAKAN, KEPATUHAN WAJIB PAJAK TERHADAP PENGGELAPAN PAJAK - Rossje Vitarimetawatty Suryaputri; Ancilla Regina Averti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
This research aims to test the effect of tax justice, taxation system, tax discrimination, taxpayer compliance against tax evasion. Independent variables in this study are taxation justice, taxation system, taxation discrimination, taxpayer compliance while the dependent variable is tax evasionThis research use primary data by handing out questionnaires to the taxpayer. 100 questionnaires had been handing out to private taxpayer in the area of West Jakarta, The method used in the research is convenience sampling. Data analytic used multiple regression analytics data. The results of this study indicate that tax justice, taxation system, tax discrimination, taxpayer compliance have a positive effect on tax evasion, while taxpayer compliance has a negative effect on tax evasion